2017
DOI: 10.1074/jbc.m117.815910
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of N-acetylglucosamine side-chain attachment to the Lancefield group A carbohydrate in Streptococcus pyogenes

Abstract: In many Lactobacillales species ( lactic acid bacteria), peptidoglycan is decorated by polyrhamnose polysaccharides that are critical for cell envelope integrity and cell shape and also represent key antigenic determinants. Despite the biological importance of these polysaccharides, their biosynthetic pathways have received limited attention. The important human pathogen, , synthesizes a key antigenic surface polymer, the Lancefield group A carbohydrate (GAC). GAC is covalently attached to peptidoglycan and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
2
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(120 citation statements)
references
References 65 publications
8
101
2
4
Order By: Relevance
“…The observation that the SMUΔsccH mutant could only be rescued from from Zn (II) toxicity and acquisition of hGIIA resistance by expression of the native sccH, suggested that the site of GroP attachment to SRPs might involve the species-specific side chains (Glc vs. GlcNAc), rather than the identical polyrhamnose backbone. Consistent with this hypothesis, the glycerol and phosphate contents in the SRP isolated from two GlcNAc-deficient mutants, 5005ΔgacL and 5005ΔgacI 22 are similar to those in 5005ΔgacH ( Fig. 7d).…”
Section: Identification Of the Enantiomeric Form Of Grop Associated Wsupporting
confidence: 78%
See 2 more Smart Citations
“…The observation that the SMUΔsccH mutant could only be rescued from from Zn (II) toxicity and acquisition of hGIIA resistance by expression of the native sccH, suggested that the site of GroP attachment to SRPs might involve the species-specific side chains (Glc vs. GlcNAc), rather than the identical polyrhamnose backbone. Consistent with this hypothesis, the glycerol and phosphate contents in the SRP isolated from two GlcNAc-deficient mutants, 5005ΔgacL and 5005ΔgacI 22 are similar to those in 5005ΔgacH ( Fig. 7d).…”
Section: Identification Of the Enantiomeric Form Of Grop Associated Wsupporting
confidence: 78%
“…GAC was released from the cell wall by sequential digestion with mutanolysin (Sigma Aldrich) and recombinant PlyC amidase 22 , and partially purified by a combination of size exclusion and ion-exchange chromatography. Mutanolysin digests contained 5 mg/mL of cell wall suspension in 0.1 M sodium acetate, pH 5.5, 2 mM CaCl 2 and 5 U/ml mutanolysin.…”
Section: Gac Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to dltA and lytR , mutation of gacI , which results in loss of the GAC GlcNAc side chain [ 45 ], increased GAS resistance to hGIIA by approximately 10-fold compared to the parental or gacI -complemented ( gacI* ) strain ( Fig 2C ). The GAC is conserved in all GAS serotypes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrates that GacI is a membrane protein that is required for the intracellular formation of undecaprenyl-P-GlcNAc [ 45 ]. Therefore, loss of GacI could alter membrane composition and fluidity to impact the activity of hGIIA on the membrane.…”
Section: Resultsmentioning
confidence: 99%